If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13 = x + 5 Reorder the terms: -13 = 5 + x Solving -13 = 5 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -13 + -1x = 5 + x + -1x Combine like terms: x + -1x = 0 -13 + -1x = 5 + 0 -13 + -1x = 5 Add '13' to each side of the equation. -13 + 13 + -1x = 5 + 13 Combine like terms: -13 + 13 = 0 0 + -1x = 5 + 13 -1x = 5 + 13 Combine like terms: 5 + 13 = 18 -1x = 18 Divide each side by '-1'. x = -18 Simplifying x = -18
| 5x+38=13x-58 | | 2x^4+5x^2=3 | | -0.333x=15 | | 6x+56=11x+11 | | -3m=5(m-8) | | v^2+3v-40=0 | | .75y=6 | | v^2+7+6=0 | | 3z-9=5z-3z | | 100=15-2.5h | | 6m=-42 | | 6050=-10x^2+335x+3700 | | 25+5+12=132 | | -12s=-120 | | -9t=36 | | 3y=42 | | 25+5+12= | | 6x^4-36x^2=0 | | 15n=-30 | | 9x-4y=15 | | 2x^2-67x+730=0 | | 7-7x=107-35x | | (2r+5)(3r^2-16r+5)=0 | | 2x-y=3 | | 7x=91 | | 2(w-7)+10w=34 | | -52-10x=7x+16 | | 3x+7=-15-8x | | 2x+10= | | 4x-y=0 | | 3x-2x=-4x-4 | | 3(x+2)=(x+1)(x-1) |